Crush - Paige, Jennifer; Edel America Records (United States : Edel America Records, 1998)
Contains the single with dance mix and instrumental.
CD 1 : Crush / (3:19) -- Crush (Dance Mix) / (3:16) -- Crush (Instrumental) / (3:19).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English